The Social Reality and Education of Children With Visual Disabilities in The Novel Anak-Anak Cahaya by Ramaditya Adikara - Adene Taqya, Hilya Ayu; Alfian Setya Nugraha (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This study aims to describe the phenomenon of social reality and education of children with visual disabilities in the novel "Children of Light" by Ramaditya Adikara and the relationship between literary works and real life using Mimetic theory and Literary Sociology approach. This study used a type of qualitative descriptive research. The source of this research is the novel Children of Light by Ramaditya Adikara by taking words, sentences, dialogues and paragraphs containing social and educational reality. The data collection technique used is by reading and recording techniques, as well as supporting data obtained from interviews to find out the social and educational picture of children with visual disabilities both in literary and real life works. The results of this study are a picture of social and educational reality, namely: (1) a picture of social reality regarding an attitude of affection, an attitude of togetherness, an attitude of caring, an attitude of tolerance, and an attitude of help. (2) a picture of educational realities such as Democratic, hard work, independent, religious and responsibility. These images are in the novel "Children of Light" which has a connection with the reflection of real life of blind disabled children in society. So it can be concluded that literary works have a relationship with real life or reality.